“Everybody Knew Čuoppomáddu Stories”. On Human/Other‑Than-Human Relations in Stuornjárga as Revealed Through the Márka‑Sámi Toponyms - De Vivo, Erika (Lagoonscapes, 2022)
The Sámi people share their ancestral homeland (Sápmi, sub/Arctic Europe) not only with animals, plants, trees, rocks, colonial-settlers and more recent immigrants but also with other-than-human beings. For centuries, the Sámi have co-constructed Sápmi’s landscape with these entities through respect and reciprocity. Despite enforced conversion, elements of Sámi Indigenous worldviews persisted. Enshrined in placenames, collective memory of interactions with other-than-human beings has been passed down through generations. The paper highlights the importance that toponyms have in transmitting cultural values, identity, and a sense of belonging.